Evaluation of nitric oxide levels in chronic periodontitis patients treated with initial periodontal therapy and probiotic food supplements: a double blind, randomized controlled clinical trial - ALTURFAN, EBRU IŞIK (TAYLOR & FRANCIS LTD, 2019)
The aim of the present study was to analyse the nitric oxide (NO) levels in gingival crevicular fluid (GCF) of patients with chronic periodontitis (CP) treated with probiotic-containing food supplements as an adjunct to initial periodontal therapy (IPT). The present study was a randomized, double blind clinical trial conducted in Yeditepe University Dental Hospital, Istanbul, Turkey. Thirty-six CP patients, with >= 2 nonmolar teeth in each quadrant with probing depth (PD) of 5-7 mm at proximal sites and radiologically detectable horizontal alveolar bone loss were randomized into two treatment groups. The test group received IPT + probiotic-containing food supplements, whereas the control group received IPT + placebo. GCF sampling was performed at the baseline and 3 and 6 months after treatment. The biochemical evaluation of NO in GCF was performed using the Griess colourimetric method. Statistical analysis was performed by using statistical software. Significant reductions in GCF volume and GCF NO levels were detected in each group after the treatments (p < 0.05). Intergroup comparison of the NO levels revealed statistically significant differences in favour of the test group at both 3 and 6-month evaluation periods (p < 0.05). Adjunctive usage of probiotic comprising food supplements to IPT yielded significant reduction of the NO levels compared to the control for up to 6 months of follow-up. The present study is registered at Thai Clinical Trials Registry (TCTR identification number: TCTR20171114003).
Keywords: Nitric oxide; gingival crevicular fluid; chronic periodontitis; initial periodontal therapy; probiotic food supplements; LACTOBACILLUS-REUTERI; DISEASE; INFLAMMATION; EXPRESSION; BIOMARKERS; LOZENGES; NITRATE